Forecasting manpower requirement in Indian veterinary and animal husbandry sector - AGRAWAL, RASHMI; RAO, DARAPUNENI RAMA; RAO, B V L N; NANDA, S K; KUMAR, INDER (The Indian Journal of Animal Sciences, 2013)
This paper presents a comprehensive assessment of demand-supply scenario for human resources in veterinary and animal husbandry sector in India. Mixed forecasting approaches are used to estimate stock and future demand. The annual demand has been computed by integrating stock projections in different sub-sectors of employment. During the last decade, supply of veterinary and animal husbandry graduates has increased at 4% per annum. The forecast indicated additional annual requirement for about 5,000 graduates and thrice more para-vets up to 2020 to meet the supply demand gap. The paper hints at strategies to support academic research and private sector participation to meet the emerging demand.